Imitations of Cloisonne Enamels in Ancient Russian Art on the Example of Archaeological Finds from the Vladimir-Suzdal Region - Stolyarova, Ekaterina K.; Kovalenko, Ekaterina S.; Murashev, Mikhail M.; Podurets, Konstantin M.; Zaytseva, Irina E.; Mukhina, Tatyana F.; Guryeva, Polina V.; Tereschenko, Elena Y.; Yatsishina , Ekaterina B. (Actual Problems of Theory and History of Art, 2024)
The design and technological features of polychrome enamels on three Old Russian (12th–13th centuries) bronze objects, an icon pendant, a kolt and a cross, found in the Vladimir-Suzdal region were studied by X-ray, synchrotron, and neutron tomography. The enamel images decorating them are similar in appearance to the cloisonné enamel technique. However, the obtained data allow us to conclude that their technology does not have the main features of either type of cloisonné enamel: European and Byzantine. In the objects under consideration, the enamels are deposited into recesses, which is not the case with European enamels, while the recesses are obtained by casting, which is not used in Byzantine cloisonné enamels. Moreover, various copper alloys used as the base material for the objects, were not used in either European or Byzantine cloisonné enamels. The study showed that the enamel inserts were not made using the cloisonné enamel technique, where metal partitions are placed on a plate or in a recess, forming cells that are subsequently filled with enamel of different colors. The order of operations was the revised: first, the enamels were applied, then the partitions were placed on certain places, and then the enamel was fired. The partitions had a decorative function, as a contour that limited the images. The products made with such a simplified technology can be considered as imitations of expensive gold items of princely-boyar attire made using the complex jewelry technique of cloisonné enamel.The work was carried out within the framework of the state assignment implementation of the National Research Centre "Kurchatov Institute" in part of X-ray tomographic studies, and the state assignment of the Institute of Archaeology of the Russian Academy of Sciences (R&D No. 122011200266-3) in terms of technological studies of ancient Russian enamels.
Keywords: Kievan Rus’; jewelry technologies; polychrome enamel; cloisonné enamel; X-ray tomography; synchrotron tomography; neutron tomography